Antifungal activity of nisin against clinical isolates of azole-resistant Candida tropicalis - Gao, Shuo; Ji, Yueyue; Xu, Shilan; Jia, Jia; Fan, Baiyuan; Zhang, Yan; Shen, Han; Zhou, Wanqing (Frontiers in Microbiology, 2024)
The rapid emergence of invasive infections caused by azole-resistant Candida tropicalis has become a public health concern, and there is an urgent need for alternative treatment strategies. Studies have demonstrated the antibacterial effects of nisin, a well-known peptide naturally produced by Lactococcus lactis subsp. lactis. However, there is scant information about the antifungal effect of nisin against C. tropicalis. The present study aims to investigate the in vitro antifungal activity of nisin against clinical isolates of azole-resistant C. tropicalis strains, as well as its inhibitory effect on biofilm formation. A total of 35 C. tropicalis strains isolated from patients with invasive fungal infections were divided into the azole-resistant group and the azole-sensitive group, containing 21 and 14 strains, respectively. The relative expression levels of the ERG11 and UPC2 genes in the azole-resistant group were higher than those in the azole-sensitive group (P < 0.0001), while no significant differences were observed in the expression levels of the MDR1 and CDR1 genes. The minimum inhibitory concentration of nisin against C. tropicalis ranged from 2 to 8 μg/mL. Nisin treatment inhibited the growth of azole-resistant C. tropicalis, with over a four-fold reduction in OD600 nm values observed at the 8-h time point, while it promoted the transition of C. tropicalis from the spore phase to the hyphal phase, as observed on cryo-scanning electron microscopy. The results of biofilm quantification using crystal violet staining indicated a significant decrease in OD570 nm values in the nisin-treated group compared to the controls (P < 0.0001). Among the 21 azole-resistant C. tropicalis strains, the biofilm formation was inhibited in 17 strains (17/21, 81%), and more than 85% inhibition of biofilm formation was observed in the representative strains. With regard to the molecular mechanisms, the expression of the BCR1 and UPC2 genes in the azole-resistant strains was down-regulated on nisin treatment (P < 0.05). In conclusion, we demonstrated, for the first time, that nisin has antifungal activity and significant anti-biofilm activity against clinical isolates of azole-resistant C. tropicalis strains. Based on the findings, nisin could be a promising alternative antifungal agent for combating azole-resistant C. tropicalis infections.